2006
DOI: 10.1021/jp063568o
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of CuIY Zeolite:  Structure and Electronic Properties

Abstract: The structural and electronic properties of the accessible Cu(I) site of a faujasite-type zeolite have been studied, by use of large cluster models and a density functional theory-based methodology. We demonstrate that the local ideal C(3) symmetry of the Cu(I) site II is broken. The Cu(I) cation is bonded to the zeolite framework by one bond of about 2.26 A and two shorter ones of 2.07 A. We demonstrate that only one cation position exists at this site. This result is also confirmed by a molecular electrostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
(71 reference statements)
5
6
0
Order By: Relevance
“…Let us first consider the bare Cu(I)-containing zeolite without adsorbed O 2 (for a discussion of the oxidation state of copper, see section 5.3). In agreement with the computational results of Sierka, Sauer and co-workers 18 and Jardillier et al, 63 with only one Al atom per ring, the Cu(I) ion is coordinated to 3 or 2 oxygen atoms for adsorption sites II and III, respectively. These O atoms are of type O2 in the case of the SII adsorption site, i.e.…”
Section: Cluster Modelssupporting
confidence: 91%
See 1 more Smart Citation
“…Let us first consider the bare Cu(I)-containing zeolite without adsorbed O 2 (for a discussion of the oxidation state of copper, see section 5.3). In agreement with the computational results of Sierka, Sauer and co-workers 18 and Jardillier et al, 63 with only one Al atom per ring, the Cu(I) ion is coordinated to 3 or 2 oxygen atoms for adsorption sites II and III, respectively. These O atoms are of type O2 in the case of the SII adsorption site, i.e.…”
Section: Cluster Modelssupporting
confidence: 91%
“…A QM region which is too small may result in artifacts. Consequently, rather large QM regions have been suggested by other authors, 18,63 but usually at the cost of the quality of the basis set. For this very reason, we performed systematic calculations with different QM regions.…”
Section: Qm/mm Calculations Vs Molecular Fragment Calculationsmentioning
confidence: 99%
“…Experiments were performed under various conditions and for zeolites prepared in different ways, thus results can differ in details. Similar results have been obtained by Jardillier et al, 42 who also have found Cu(I) only within the 6T ring plane. Our results, showing site III significantly less stable (about 100 kJ mol À1 ) than sites II and I 0 (Table 5), agree with these observations.…”
Section: Cu(i) Sitingsupporting
confidence: 90%
“…The QM-Pot approach is particularly useful for extended systems such as zeolites. 29 Previous computational studies on the Cu(I)-FAU system used free cluster models [39][40][41][42][43][44][45] and did not lead to a reliable assignment of CO stretching frequencies. The QM-Pot method gives more reliable results than free cluster models and is computationally less demanding than periodic quantum mechanical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Using tetrahedral coordinates that have already been determined by various experiments, a reasonable model can be built to simulate the zeolite framework. Because the location and distribution of heteroatoms in the framework are connected to the structural properties of zeolites, theoretical studies give a better understanding of the nature of isomorphically substituted zeolites [33,34].…”
Section: Introductionmentioning
confidence: 99%